2002
DOI: 10.1162/089892902760807159
|View full text |Cite
|
Sign up to set email alerts
|

Components of Switching Intentional Set

Abstract: Despite the intuition that we can shift cognitive set on instruction, some behavioral studies have suggested that set shifting might only be accomplished once we engage in performance of the new task. It is possible that set switching consists of more than one component cognitive process and that the component processes might segregated in time. We recorded event-related potentials (ERPs) during two set-switching tasks to test whether different component processes were responsible for (i) set initiation and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

48
233
3
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(286 citation statements)
references
References 55 publications
48
233
3
2
Order By: Relevance
“…A role for posterior parietal cortex in processing response alternatives finds additional support in the broader cognitive control literature (37,38). A temporal shift from mid-VLPFC (conceptual) to inferior parietal (response) cortex may also parallel electroencephalogram evidence that TS is accompanied by an early frontal component (Ϸ300-500 ms) followed by a subsequent parietal component (Ϸ500-1,000 ms) (39)(40)(41).…”
Section: Resultsmentioning
confidence: 88%
“…A role for posterior parietal cortex in processing response alternatives finds additional support in the broader cognitive control literature (37,38). A temporal shift from mid-VLPFC (conceptual) to inferior parietal (response) cortex may also parallel electroencephalogram evidence that TS is accompanied by an early frontal component (Ϸ300-500 ms) followed by a subsequent parietal component (Ϸ500-1,000 ms) (39)(40)(41).…”
Section: Resultsmentioning
confidence: 88%
“…Detailed behavioral analyses in normal human subjects have revealed that inhibition of proactive interference is one of the essential component processes recruited at the time of switching one task to another (9,10). In support of the above findings, neuroimaging studies have demonstrated prominent activation in the lateral prefrontal cortex during set shifting͞task switching (11)(12)(13)(14)(15)(16)(17)(18).…”
mentioning
confidence: 71%
“…However, previous behavioral studies have demonstrated that the interference continues even after the first inhibition trial over the time scale of a minute or so, and therefore the previous set needs to be inhibited even after the first trial to avoid perseverative errors (9). Previous investigations of inhibitory mechanisms have focused on the first inhibition trial, whether the first trial was given immediately after the change (11)(12)(13)(14)(15)(16)(17)(18) or separated away from the change (19). Despite the abundant knowledge about the inhibitory mechanisms recruited at the first inhibition trial, little is known about the neural mechanisms responsible for the inhibition of the prolonged interference that persists long after the first inhibition trial.…”
mentioning
confidence: 99%
“…This positivity was interpreted by some authors as P3b modulation (Barceló, Periáñez, & Knight, 2002;Kieffaber & Hetrick, 2005;Nicholson, Karayanidis, Poboka, Heathcote, & Michie, 2005;Tieges, Snel, Kok, Plat, & Ridderinkhof, 2007) and by others as a reduction in CNV (Hsieh & Chen, 2006;Lorist et al, 2000). The posterior positivity is sometimes preceded by an early (100 to 300-ms) or moderately early (300 to 500-ms) anterior positivity (Astle, Jackson, & Swainson, 2008;Rushworth et al, 2002) or followed by a late (500 to 1,000-ms) anterior negativity (Astle et al, 2008;Lavric, Mizon, & Monsell, 2008;Moulden et al, 1998). In other studies, the posterior positivity was preceded by an early anterior negativity (Poulsen, Luu, Davey, & Tucker, 2005).…”
mentioning
confidence: 96%
“…Many of these studies have reported that in comparison with task repeat trials, there was a switch-related central-posterior positivity occurring about 400 ms after the cue (Hsieh, 2002;Karayanidis, Coltheart, Michie, & Murphy, 2003;Miniussi, Marzi, & Nobre, 2005;Moulden et al, 1998;Rushworth, (Slagter, Kok, Mol, Talsma, & Kenemans, 2005). This positivity was interpreted by some authors as P3b modulation (Barceló, Periáñez, & Knight, 2002;Kieffaber & Hetrick, 2005;Nicholson, Karayanidis, Poboka, Heathcote, & Michie, 2005;Tieges, Snel, Kok, Plat, & Ridderinkhof, 2007) and by others as a reduction in CNV (Hsieh & Chen, 2006;Lorist et al, 2000).…”
mentioning
confidence: 99%